Bioethics Teaching and Assessment: My Experience of Three Institutes - Rafique, Zoheb (Bangladesh Journal of Bioethics, 2014)
This paper describes my experience of teaching bioethics in different institutes and degree courses at undergraduate level. Bioethics is being taught to improve the understanding of the ethical issues in the field of medicine. The students are being trained in bioethics to recognize and resolve different ethical dilemmas and also to combat the situations where ethical analysis is needed. This paper also focuses on teaching and assessment methods for undergraduate courses. DOI: http://dx.doi.org/10.3329/bioethics.v5i2.19577 Bangladesh Journal of Bioethics 2014; 5(2):44-48